2021
DOI: 10.1093/ve/veab003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel avian and mammalian deltaviruses provides new insights into deltavirus evolution

Abstract: Hepatitis delta virus (HDV) is a satellite virus that requires hepadnavirus envelope proteins for its transmission. Although recent studies identified HDV-related deltaviruses in certain animals, the evolution of deltaviruses, such as the origin of HDV and the mechanism of its coevolution with its helper viruses, is unknown, mainly because of the phylogenetic gaps among deltaviruses. Here we identified novel deltaviruses of passerine birds, woodchucks, and white-tailed deer by extensive database searches and m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 66 publications
1
46
0
5
Order By: Relevance
“…Similarly, RDeV, OvirDeV, and tgDeV infections do not seem to be limited to the liver, as the virus’s sequence reads have been obtained from at least two different tissues. On occasion, data were consistent with a broad range or even systemic infection [ 23 , 25 , 27 ].…”
Section: Discovery Of Hdv-like Virusesmentioning
confidence: 84%
See 3 more Smart Citations
“…Similarly, RDeV, OvirDeV, and tgDeV infections do not seem to be limited to the liver, as the virus’s sequence reads have been obtained from at least two different tissues. On occasion, data were consistent with a broad range or even systemic infection [ 23 , 25 , 27 ].…”
Section: Discovery Of Hdv-like Virusesmentioning
confidence: 84%
“…A central component of these hypotheses is that HDV had been found, until recently, only in humans. Yet, several viruses closely related to HDV have now been detected in non-human species in the absence of any hepadnavirus [ 22 , 23 , 24 , 25 , 26 , 27 ]. Further studies are warranted to ascertain whether these agents represent satellite viruses dependent on a helper virus for their propagation, or alternatively, they are examples of a novel family of autonomous viroid-like agents in animals, whose transmission would occur by conventional receptor-mediated means.…”
Section: Current Hypotheses Of Hdv Originmentioning
confidence: 99%
See 2 more Smart Citations
“…These HDV-like viruses were detected in different organs (brain, liver, kidney, gut, lung) and persisted completely in the absence of a co-infection with HBV-related hepadnaviruses. A recent study performing a transcriptome data analysis also identified novel HDV-related sequences in birds and mammals including the zebra finch (taeniopygia guttata), common canary (serinus canaria), Gouldian finch (erythrura gouldiae), Eastern woodchuck (marmota monax), and white-tailed deer (odocoileus virginianus) [63]. Moreover, snake HDV was able to replicate in different snake, monkey, and human cell lines after their transfection with a plasmid expressing snake HDV genomes.…”
Section: Natural Hosts Of Hdv and Hdv-related Virusesmentioning
confidence: 94%